The impact of regulation on economic growth in developing countries: a cross-country analysis - Jalilian, Hossein; Kirkpatrick, Colin; Parker, David (Elsevier, 2007)
The role of an effective regulatory regime in promoting economic growth and development has generated considerable interest among researchers and practitioners in recent years. In particular, building effective regulatory structures in developing countries is not simply an issue of the technical design of the most appropriate regulatory instruments, it is also concerned with the quality of supporting regulatory institutions and capacity. This paper explores the role of state regulation using an econometric model of the impact of regulation on growth. The results based on two different techniques of estimation suggest a strong causal link between regulatory quality and economic performance.
Keywords: economic growth; regulation; governance; developing countries; institutions